Smooth polymers charge negatively: Controlling contact electrification polarity in polymers. (15th December 2022) - Verners, Osvalds; Lapčinskis, Linards; Ģermane, Līva; Kasikov, Aarne; Timusk, Martin; Pudzs, Kaspars; Ellis, Amanda V.; Sherrell, Peter C.; Šutka, Andris
Abstract: Contact electrification is a powerful tool to harvest energy from mechanical motion. However, current models of contact electrification at polymer | polymer interfaces only explain charge transfer for contact between chemically dissimilar polymers. Recently, strong contact electrification between chemically identical polymer surfaces has been observed. Understanding contact electrification between chemically identical polymers is a key issue in developing a wholistic model for polymer triboelectrification. Herein, we present a combined experimental and computational approach to develop a model of the contact electrification between chemically identical polymers. The model developed describes how the relative surface roughness influences surface charge. The chemically identical polymer surfaces show an increase in the surface charge when the difference in surface roughness is increased. Further, the roughest surface was found to present a positive surface charge, and the smoother surface a negative charge. These observations were justified though modelling of a consistently lower strain in rougher surfaces during contact-separation. Molecular dynamics simulations demonstrated the relationship between this strain with bond-scission and charged material transfer. It was found that a negative charged fragment has a higher statistical probability to be transferred due to smaller scission / desorption energies. This comparison of surface roughness can be extended to dissimilar polymer interfaces and will enable engineering of highly efficient triboelectric nanogenerator (TENG) devices in the future. Graphical Abstract: Combined experimental and computational approach to develop a model of the contact electrification between chemically identical polymers which describes how the relative surface roughness influences surface charge. The negatively charged fragment identified to have a higher statistical probability to be transferred between surfaces due to smaller scission / desorption energies. ga1 Highlights: Model to explain/control contact electrification of chemically identical polymers. Topography driven control: rough surface shows a positive charge, smooth - negative. Bond scission and material transfer relates to lower strain in rough surfaces. Charge of transferred fragments is determined by scission/desorption energies. Generalized approach for contact electrification proposed for all kinds of polymers.